Minimum wage effects on job attachment: A gender perspective - Eva García-Morán; Ming-Jin Jiang; Heiko Rachinger (Journal of Economics and Statistics, 2024)
We examine whether the effects of the introduction of a minimum wage on low-pay employment duration in Germany in 2015 are heterogeneous by gender. In order to disentangle the effects on women and men, we estimate a duration model with unobserved heterogeneity in which we allow gender differences and differences before and after the introduction of the minimum wage. We find that the reform does affect women and men differently, in particular, it mainly increases men's job attachment. These gender differences in job attachment are the strongest for full-time employment. In consequence, although the minimum wage may have been set up as a gender-neutral instrument, in an indirect way, it affects women and men differently. We discuss different mechanisms that could account for our result and carry out several robustness checks.
Keywords: J31; J2; J38; J16; 330; duration; employment; gender differences; minimum wage